Akuntabilitas Pengelolaan Keuangan Daerah Dilihat Dari Penyajian Laporan Keuangan Dan Aksesibilitas Laporan Keuangan Pada Kantor Bkd Provinsi Sumatera Barat Tahun 2020 - Nursal Nursal; Febryandhie Ananda (JURNAL PUNDI, 2023)
This study aims to determine the influence of the Presentation of Financial Statements and Accessibility of Financial Statements on the Accountability of Regional Financial Management at the BKD office of West Sumatra Province the year is 2020. With the purposive sampling method as many as 40 respondents from BKD office employees. Using the SPSS 25 Application to test: Instrument Test (Validity Test, Reliability Test), Classical Assumption Test (Normality Test, Multicollinearity Test, Heterochedasticity Test) Hypothesis Test (T Test, Determination Test, Simple / Multiple Linear Regression Test). After testing, it was found that the presentation of financial statements has an influence on accountability of Regional Financial Management, which is mean that the hipotesis is accepted. Accessibility of Financial Statements has not influence on accountability of   Regional Financial Management, which is mean  that the hipotesis is not accepted.